Urinary phthalate metabolite and bisphenol A associations with ultrasound and delivery indices of fetal growth. (September 2016) - Ferguson, Kelly K.; Meeker, John D.; Cantonwine, David E.; Chen, Yin-Hsiu; Mukherjee, Bhramar; McElrath, Thomas F.
Abstract: Growth of the fetus is highly sensitive to environmental perturbations, and disruption can lead to problems in pregnancy as well as later in life. This study investigates the relationship between maternal exposure to common plasticizers in pregnancy and fetal growth. Participants from a longitudinal birth cohort in Boston were recruited early in gestation and followed until delivery. Urine samples were collected at up to four time points and analyzed for concentrations of phthalate metabolites and bisphenol A (BPA). Ultrasound scans were performed at four time points during pregnancy for estimation of growth parameters, and birthweight was recorded at delivery. Growth measures were standardized to a larger population. For the present analysis we examined cross-sectional and repeated measures associations between exposure biomarkers and growth estimates in 482 non-anomalous singleton pregnancies. Cross-sectional associations between urinary phthalate metabolites or BPA and growth indices were imprecise. However, in repeated measures models, we observed significant inverse associations between di-2-ethylhexyl phthalate (DEHP) metabolites and estimated or actual fetal weight. An interquartile range increase in summed DEHP metabolites was associated with a 0.13 standard deviation decrease in estimated or actual fetal weight (95% confidence interval = − 0.23, − 0.03). Associations were consistent across different growth parameters (e.g., head circumference, femur length), and by fetal sex. No consistent associations were observed for other phthalate metabolites or BPA. Maternal exposure to DEHP during pregnancy was associated with decreased fetal growth, which could have repercussive effects. Highlights: Exposure to phthalates and BPA in pregnancy may impact development of the fetus. We measured exposure biomarkers at 4 visits during gestation on 482 women. We used ultrasound scans from pregnancy and birthweight to examine fetal growth. Urinary di-2-ethylhexyl phthalate metabolites were associated with reduced growth. This is the first study with a robust repeated measures design to detect this relationship.